Can one determine the density of an individual synthetic macromolecule?12. Issue 32 (30th July 2019) - Messmer, Daniel; Sánchez-Ferrer, Antoni; Tacke, Sebastian; Yu, Hao; Nüsse, Harald; Klingauf, Jürgen; Wepf, Roger; Kröger, Martin; Halperin, Avraham; Mezzenga, Raffaele; Schlüter, A. Dieter
Abstract : The determination of volumetric mass densities of dendronized polymers was attempted, utilizing the measurable physical dimensions these synthetic molecular objects possess. Abstract : Dendronized polymers (DPs) are large and compact main-chain linear polymers with a cylindrical shape and cross-sectional diameters of up to ∼15 nm. They are therefore considered molecular objects, and it was of interest whether given their experimentally accessible, well-defined dimensions, the density of individual DPs could be determined. We present measurements on individual, deposited DP chains, providing molecular dimensions from scanning and transmission electron microscopy and mass-per-length values from quantitative scanning transmission electron microscopy. These results are compared with density values obtained from small-angle X-ray scattering on annealed bulk specimen and with classical envelope density measurements, obtained using hydrostatic weighing or a density gradient column. The samples investigated comprise a series of DPs with side groups of dendritic generations g = 1–8. The key findings are a very large spread of the density values over all samples and methods, and a consistent increase of densities with g over all methods. While this work highlights the advantages and limitations of the applied methods, it does not provide a conclusive answer to the question of which method(s) to use for the determination of densities of individual molecular objects. We are nevertheless confident that these first attempts to answer this challenging question will stimulate more research into this important aspect of polymer and soft matter science.